2007
DOI: 10.1111/j.1467-2679.2007.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

The introduction of the European bitterling (Rhodeus amarus) to west and central Europe

Abstract: The European bitterling is considered to be a native species over much of its present range in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 50 publications
2
83
0
Order By: Relevance
“…All other bitterling species are restricted to East Asia where they are abundant [12]. Rhodeus amarus is a relatively thermophilic species [25] and expanded across Europe from glacial refugia in the Pontic and Mediterranean regions in warmer climatic periods of the Quaternary [22,23,26]. Two distinct phylogeographic clades colonized much of continental Europe independently, each originating from the same refugium.…”
Section: Introductionmentioning
confidence: 99%
“…All other bitterling species are restricted to East Asia where they are abundant [12]. Rhodeus amarus is a relatively thermophilic species [25] and expanded across Europe from glacial refugia in the Pontic and Mediterranean regions in warmer climatic periods of the Quaternary [22,23,26]. Two distinct phylogeographic clades colonized much of continental Europe independently, each originating from the same refugium.…”
Section: Introductionmentioning
confidence: 99%
“…Except for Rhodeus amarus (Bloch, 1782) and Proterorhinus marmoratus (Pallas, 1814) syn. Protherorhinus semilunaris (Heckel, 1837) that probably spread via the Danube River hundreds of years ago (Harka & Bíró 2007;Van Damme et al 2007), the first introductions occurred in the beginning of the 20 th century, when Oncorhynchus mykiss (Walbaum, 1792) and Salvelinus fontinalis (Mitchill, 1814) followed by Coregonus maraena (Bloch, 1779) a few years later (Table 1) were imported (Holčík 1969;Volf & Hubáček 1930). In the same period Ameiurus nebulosus (Lesueur, 1819) penetrated from neighbouring countries (mainly Hungary) (Balon 1966).…”
Section: Resultsmentioning
confidence: 99%
“…Common carp that is native to Danube was probably translocated together with bitterling (Rhodeus amarus) throughout Europe in the 12 th or 13 th century (Kottelat & Freyhof 2007;Van Damme et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…fish species mussel initial glochidia load (median, range) figure 2), whereas the development success of native A. anatina showed an apparent coevolutionary signal in host suitability (Kruskal -Wallis: H 4,44 ¼ 32.3, p , 0.001, figure 2), with low success in species of east Asian origin (present in Europe for several decades) [17] and R. amarus (itself of east Asian origin and descent, with its ancestor colonizing southern Europe 2-3 Ma [18], and most of continental Europe during the Holocene [8,9]). Notably, very low development success under experimental conditions indicated that R. amarus is a non-functional host of A. anatina.…”
Section: Results and Discussion (A) Impact Of Anodonta Woodiana On Rhmentioning
confidence: 99%
“…Bitterling are of east Asian origin, with more than 50 species distributed in east Asia and a single species in Europe [7]. European R. amarus has expanded relatively recently (centuries to millennia before present) from the Black Sea region into central and west Europe [8,9] where it exploits evolutionarily naive mussel populations [10].…”
Section: Introductionmentioning
confidence: 99%